Virtual Reality Analgesia for Children With Large Severe Burn Wounds During Burn Wound Debridement - Hoffman, Hunter G.; Patterson, David R.; Rodriguez, Robert A.; Peña, Raquel; Beck, Wanda; Meyer, Walter J. (Frontiers in Virtual Reality, 2020)
The objective of this study was to compare the effect of adjunctive virtual reality vs. standard analgesic pain medications during burn wound cleaning/debridement. Participants were predominantly Hispanic children aged 6-17 years of age, with large severe burn injuries (TBSA = 44%) reporting moderate or higher baseline pain during burn wound care. Using a randomized between-groups design, participants were randomly assigned to one of two groups, a) the Control Group = pain medications only or b) the VR Group = pain medications + virtual reality. A total of 50 children (88% Hispanic) with large severe burns (mean TBSA > 10%) received severe burn wound cleaning sessions. For the primary outcome measure of worst pain (intensity) on Study Day 1, using a between groups ANOVA, burn injured children in the group that received virtual reality during wound care showed significantly less pain intensity than the No VR control group, (mean worst pain ratings for the No VR group = 7.46 (SD = 2.93) vs 5.54 (SD = 3.56), f(1,48) = 4.29, < .05, MSE = 46.00. Similarly, one of the secondary pain measures, “lowest pain during wound care” was significantly lower in the VR group, No VR = 4.29 (SD = 3.75) vs 1.68 (2.04) for the VR group, F(1,47) = 9.29, < .005, MSE = 83.52 for Study Day 1. The other secondary pain measures showed the predicted pattern on Study Day 1, but were non-significant. Regarding whether VR reduced pain beyond Study Day 1, absolute change in pain intensity (analgesia = baseline pain minus the mean of the worst pain scores on Study days 1-10) was significantly greater for the VR group, F(1,48) = 4.88, p < .05, MSE = 34.26, partial eta squared =.09, but contrary to predictions, absolute change scores were non-significant for all secondary measures.